Neurobiological findings associated with high cognitive performance in older adults: a systematic review - Borelli, Wyllians Vendramini; Schilling, Lucas Porcello; Radaelli, Graciane; Ferreira, Luciana Borges; Pisani, Leonardo; Portuguez, Mirna Wetters; da Costa, Jaderson Costa (International psychogeriatrics, 2018)
ABSTRACTObjectivesto perform a comprehensive literature review of studies on older adults with exceptional cognitive performance. DesignWe performed a systematic review using two major databases (MEDLINE and Web of Science) from January 2002 to November 2017. ResultsQuantitative analysis included nine of 4,457 studies and revealed that high-performing older adults have global preservation of the cortex, especially the anterior cingulate region, and hippocampal volumes larger than normal agers. Histological analysis of this group also exhibited decreased amyloid burden and neurofibrillary tangles compared to cognitively normal older controls. High performers that maintained memory ability after three years showed reduced amyloid positron emission tomography at baseline compared with high performers that declined. A single study on blood plasma found a set of 12 metabolites predicting memory maintenance of this group. ConclusionStructural and molecular brain preservation of older adults with high cognitive performance may be associated with brain maintenance. The operationalized definition of high-performing older adults must be carefully addressed using appropriate age cut-off and cognitive evaluation, including memory and non-memory tests. Further studies with a longitudinal approach that include a younger control group are essential.